Money and Marriage: A Spending Plan - Josephine Turner; Nayda I. Torres; Vervil Mitchell; Michael Gutter (EDIS)
Revised! FCS-7012, a 5-page fact sheet by Josephine Turner, Nayda I. Torres, Vervil Mitchell, and Michael Gutter, encourages couples to establish a spending plan and provides five key questions to keep in mind. Published by the UF Department of Family Youth and Community Sciences, December 2008.